2018
DOI: 10.1038/s41467-018-02883-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering yeast for the production of breviscapine by genomic analysis and synthetic biology approaches

Abstract: The flavonoid extract from Erigeron breviscapus, breviscapine, has increasingly been used to treat cardio- and cerebrovascular diseases in China for more than 30 years, and plant supply of E. breviscapus is becoming insufficient to satisfy the growing market demand. Here we report an alternative strategy for the supply of breviscapine by building a yeast cell factory using synthetic biology. We identify two key enzymes in the biosynthetic pathway (flavonoid-7-O-glucuronosyltransferase and flavone-6-hydroxylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
149
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 57 publications
0
149
1
3
Order By: Relevance
“…CYP706C55 was identified as the second enzyme in the prunasin biosynthetic pathway in E. cladocalyx. Three CYP706 members from other plant species have been functionally characterized previously and demonstrated to catalyze oxygenation reactions: CYP706B1 from cotton (Gossypium arboruem; Luo et al, 2001), CYP706M1 from Alaska cedar (Callitropsis nootkatensis), and a CYP706X from Erigeron breviscapus (Liu et al, 2018). In contrast, CYP706C55 catalyzes an unusual CYP reaction, which is the dehydration of phenylacetaldoxime to phenylacetonitrile.…”
Section: Cyp706c55 Catalyzes An Atypical Cyp Reactionmentioning
confidence: 99%
“…CYP706C55 was identified as the second enzyme in the prunasin biosynthetic pathway in E. cladocalyx. Three CYP706 members from other plant species have been functionally characterized previously and demonstrated to catalyze oxygenation reactions: CYP706B1 from cotton (Gossypium arboruem; Luo et al, 2001), CYP706M1 from Alaska cedar (Callitropsis nootkatensis), and a CYP706X from Erigeron breviscapus (Liu et al, 2018). In contrast, CYP706C55 catalyzes an unusual CYP reaction, which is the dehydration of phenylacetaldoxime to phenylacetonitrile.…”
Section: Cyp706c55 Catalyzes An Atypical Cyp Reactionmentioning
confidence: 99%
“…trans-Cinnamic acid and p-hydroxycinnamic acid serve as starting compounds for the production of many commercially valuable chemicals, such as styrene, 4-hydroxystyrene, caffeic acid and flavonoids (Figs 3 and 4). [79][80][81] Liu et al 79 reported the production of breviscapine (one of the flavonoids) derived from an extended L-Phe pathway in engineered yeast in which the two major active ingredients of breviscapine reached 108 and 185 mg L −1 , respectively. 46 trans-Cinnamic acid also can be converted into p-hydroxycinnamic acid catalyzed by cinnamate 4-hydroxylase (C4H).…”
Section: -Phenylethanol and Tyrosol [2-(4-hydroxyphenyl) Ethanol]mentioning
confidence: 99%
“…To solve these problems, the microbial production of these compounds has been studied extensively. [79][80][81] Liu et al 79 reported the production of breviscapine (one of the flavonoids) derived from an extended L-Phe pathway in engineered yeast in which the two major active ingredients of breviscapine reached 108 and 185 mg L −1 , respectively.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
“…In S. baicalensis , the biosynthetic genes of the root-specific compounds baicalein and norwogonin have been functionally identified, providing an important basis for studying the biosynthesis and regulation of the natural products that make up Huang Qin [14,15]. Recently, the in vitro production of baicalein and scutellarein in Escherichia coli and Saccharomyces cerevisiae has been carried out based on the guidance of synthetic biology [16,17], but the metabolic engineering of these compounds still faces considerable challenges, including the discovery and optimization of biological components. The Salvia miltiorrhiza genome from the Lamiaceae family provides useful information associated with secondary metabolism for the rapid functional identification of biosynthetic and regulatory genes [1823].…”
Section: Introductionmentioning
confidence: 99%